Evaluasi Integrasi ITIL dan COBIT 5 untuk Manajemen Layanan TI ICRM+ - Kusuma Ayu, Karisma; Utomo, Agus Prasetyo; Mariana, Novita (Jurnal Informatika, 2025)
This study evaluates the effectiveness of integrating ITIL and COBIT frameworks in enhancing IT service quality in the "ICRM Plus" application and supporting organizational strategic goals. Data were collected through user surveys, measuring the consistency and variance in perceptions of service quality. The results indicate that the integration is not fully effective, with overall perceptions being neutral to slightly positive, suggesting significant room for improvement. Key areas requiring attention include strategy communication, incident response, and continuous service improvement. Statistical analysis of mean scores and standard deviations highlights inconsistencies in implementation and communication, which may hinder optimal support of IT services towards strategic objectives. The study emphasizes the importance of better coordination and consistent standard application across departments. Practical implications suggest the need for improvements in IT service management to achieve higher service quality. Future research could explore deeper correlations and conduct longitudinal studies to assess the impact of the recommended improvements.